2018
DOI: 10.1002/hon.2494
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal T‐cell lymphoma with enteropathy‐associated T‐cell lymphoma‐like features arising in the setting of adult autoimmune enteropathy

Abstract: Enteropathy-associated T-cell lymphoma is regarded as a dismal, late complication of coeliac disease, though a single case of T-cell lymphoma with such features arising in the setting of autoimmune enteropathy of the adult has been reported to date. We aim to describe the case of a 41-year-old woman complaining of severe malabsorption syndrome, who was diagnosed with autoimmune enteropathy based on the presence of flat intestinal mucosa unresponsive to any dietary restriction and positivity for enterocyte auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 20 publications
(52 reference statements)
0
4
0
Order By: Relevance
“…Development of EATL in patients with AIE has been sporadically reported, but this has not occurred in our case series including 70 patients after 4 years of follow-up (51,52). In contrast to RCD type 2 where phenotypical analysis can accurately identify a premalignant IEL population, in AIE, no such population is present and patients are therefore screened with the less specific TCRG clonality analysis (19).…”
Section: Discussionmentioning
confidence: 71%
“…Development of EATL in patients with AIE has been sporadically reported, but this has not occurred in our case series including 70 patients after 4 years of follow-up (51,52). In contrast to RCD type 2 where phenotypical analysis can accurately identify a premalignant IEL population, in AIE, no such population is present and patients are therefore screened with the less specific TCRG clonality analysis (19).…”
Section: Discussionmentioning
confidence: 71%
“…Likewise, the Mayo Clinic group reported that IELs are increased in 50% of AIE patients[ 7 ]. Moreover, IEL might be related to the process of AIE proceeding to enteropathy associated T cell lymphoma[ 19 ]. The number of apoptotic bodies is increased in approximately half of our duodenal and ileal biopsies and in approximately half of the AIE cases reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Patients affected by CVID enteropathy are burdened by a high mortality, 33 39 mainly due to development of infectious and malignant complications. Also patients with AE can develop lymphoproliferative complications, 35 40 and an American study showed an increased mortality in patients with AE, comparable to those affected by refractory CD. 41 …”
Section: Long-term Outcomes and Mortalitymentioning
confidence: 99%